Analisis Semiotika dan Representasi Emotional Healing dalam Lagu “Perayaan Mati Rasa” Karya Umay Shahab Ft. Natania Karin - Fadia Rachma Putri; Agustina Kusuma Dewi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The phenomenon of emotional healing has become increasingly prominent in popular culture as the younger generation experiences increasing loss, emotional exhaustion, and numbness. Popular music serves as a medium of expression, representing these emotional dynamics through poetic language and symbolic structures. This study aims to analyze the emotional representation of healing in Umay Shahab's song